A comparison of the onset time of complete blockade of the sciatic nerve in the application of ropivacaine and its equal volumes mixture with lidocaine: a double-blind randomized study - Piacherski Valery (Korean Journal of Anesthesiology, 2013)
BackgroundThe purpose of the current study is to create a new mixture of local anesthetics-one with a short time of block development and short action term (5 ml of 1% lidocaine solution) and another with a longer time of anesthesia development and a long analgetic effect (5 ml of 0.75% ropivacaine)-for use during surgical operations on extremities. The primary end point was the development of the complete sensory block of the sciatic nerve.MethodsSixty blocks of sciatic nerve were used in a double-blind randomized research, under ultrasonic guidance, using an electric stimulator with the peripheral nerves. Sixty patients were divided into 3 equal groups. In the first group, a sciatic nerve block was performed with 5 ml of 0.75% ropivacaine solution (37.5 mg); in the second group, 10 ml of 0.75% ropivacaine solution (75 mg) was used and, in the third group, a mixture of 5 ml of 0.75% ropivacaine (as above) and 5 ml of 1% lidocaine solution (50 mg) was used. The assessment of the time required for developing sensory and motor blocks was carried out from the beginning of local anesthetic solution injection in the fascial sheath of the sciatic nerve.ResultsDemographic data of patients were identical in the three sample groups. The time required for achieving a complete motor and sensory block was reduced due to the mix of the 1% lidocaine solution with the 0.75% ropivacaine solution. The time required for achieving a complete sensory block in groups treated with 5 and 10 ml ropivacaine was 45 (40-48) and 30 (28-30) min, respectively, in contrast with 12 (10-13) min when the mixture of anesthetics was applied (P < 0.01). There was no difference in analgesic duration in the postoperative period among groups at P > 0.05.ConclusionsThe mixture of 5 ml of 1% lidocaine with 5 ml of 0.75% ropivacaine leads to a reduction in the time required for the development of complete sensory and motor blocks of the sciatic nerve, without reducing postoperative analgesia time.